A ética do habitar finito: The ethics of finite dwell - Uribe Miranda, Luis (Modernos & Contemporâneos - International Journal of Philosophy [issn 2595-1211], 2023)
In this article we attempt to think of the ethics of finite dwell in the context of the serious environmental problems that affect the planet. The proposal is: if we accept the thesis according to which the ethics of duty and responsibility are insufficient in the face of current problems, on one hand, and accept the defunding of ethics as a starting point, on the other hand, the possibility opens up for ethics of finite dwelling which, in turn, presupposes a negative moral experience. To this end, first, we present the concept of dwell by Martin Heidegger and, secondly, the concept of negative moral experience by Humberto Giannini. In this relationship, we develop a second-degree reflection, that is, an ethics of finite dwell. The finitude and essential mortality of man and the earth thought of in its radical nature open up possibilities of meaning to generate a new way of inhabiting the planet. Keywords: Ethics; Dwell; Martin Heidegger; Humberto Giannini; Mortality